Pengaruh Tiktok Sebagai Media Pembelajaran Seksualitas Pada Siswa Sekolah Dasar - Wahyuningsih, Nining; Fatihaturosyidah, Fatihaturosyidah (Didaktika, 2022)
The title of the research is "The Effect of TikTok as a Media for Learning Sexuality Knowledge in Elementary School Students" with correlational quantitative methods. Aims to reveal a picture of the influence of TikTok as a medium for learning sexuality knowledge for elementary school students and reveal what aspects are influential on using TikTok as a medium for learning sexuality knowledge for elementary school students. The population used by Cipanas Elementary School students in the Cipanas Environment is 10 students who have TikTok. With a questionnaire instrument given to students and supported by data from observations and interviews. The location of this research is the Cipanas environment. After the data is collected, the next step is data analysis. From the data analysis stage, getting the results of TikTok as a learning medium has no effect on sexuality knowledge in elementary school students. Although it has a variable that has no effect, the relationship between variables x and y from this study is positive, which means that the lower the influence of TikTok, the lower the knowledge of sexuality. And the level of correlation in this study is stated to be low.